2010
DOI: 10.1007/s00535-009-0182-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal follicular lymphoma: review of the literature

Abstract: Gastrointestinal follicular lymphoma (GI-FL) is a relatively rare disease, accounting for only 1%-3.6% of gastrointestinal non-Hodgkin's lymphoma. Although the duodenum and terminal ileum are considered to be the most common sites of origin, the development of wireless capsule endoscopy and double-balloon enteroscopy has increased the detection of GI-FL in every part of the small intestine. Approximately 70% of patients with GI-FL are estimated to have multiple lesions throughout the entire gastrointestinal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
150
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(168 citation statements)
references
References 120 publications
17
150
0
Order By: Relevance
“…17 Three of our cases were intestinal follicular lymphoma-two in the duodenum and one in the stomach-all three achieved complete remission after treatment with no documented spread to other sites. Lobetti-Bodoni et al 18 studied 153 follicular lymphoma patients o40 years in comparison with 850 patients 440 years, and found that younger patients had longer overall survival and longer cause-specific survival.…”
Section: Discussionmentioning
confidence: 61%
“…17 Three of our cases were intestinal follicular lymphoma-two in the duodenum and one in the stomach-all three achieved complete remission after treatment with no documented spread to other sites. Lobetti-Bodoni et al 18 studied 153 follicular lymphoma patients o40 years in comparison with 850 patients 440 years, and found that younger patients had longer overall survival and longer cause-specific survival.…”
Section: Discussionmentioning
confidence: 61%
“…18 In Japan, GI tract lesions are usually examined by GI endoscopy with biopsy as routine practice. 6 To our knowledge, there are only a few reports of the flow cytometric analysis of endoscopic biopsy specimens for the diagnosis of BCL. 7,19,20 FCM is accurate and quantitative.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 If GI tract lesions are suspected, gastrointestinal endoscopy with biopsy is performed as routine practice in Japan. 6 Previously, we reported that FCM was useful for evaluating B-cell clonality in endoscopic biopsy specimens from 10 patients with GI tract BCL. 7 We extended our work to confirm these results in a large number of patients with GI tract BCL.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review of 249 cases (244 from the literature and 5 new cases) of GI follicular lymphoma, 41 it was noted that the demographics were similar to nodal follicular lymphoma (M:F 1:1; median age 56 years). The majority occurred in the duodenum (usually as polyps rather than obstructing lesions) or small intestine and in contrast to nodal follicular lymphoma, the majority of GI follicular lymphomas present in clinical stages I/II (93.2%).…”
Section: Extranodal Marginal Zone Lymphoma Of Mucosa-associated Lymphmentioning
confidence: 99%
“…41,42 Morphologically the infiltrate consists of either a single abnormal follicle or small groups of neoplastic follicles, which may be limited to the mucosa or extend more deeply through the wall (Figure 2). The immunophenotype of GI follicular lymphoma is identical to the nodal counterpart with expression of pan-B-cell markers, CD10 and BCL6 (Figure 2).…”
Section: Extranodal Marginal Zone Lymphoma Of Mucosa-associated Lymphmentioning
confidence: 99%